Interaction between CASP8AP2 and ZEB2-CtBP2 Regulates the Expression of LEF1. (18th August 2022) - Wang, Chan-Juan; Jia, Ming-Zhu; Deng, Li-Ping; Li, Wei-Jing; Zhang, Qing; Zhang, Tong-Jia; Li, Shu-Yan; Cui, Lei; Li, Zhi-Gang
Abstract: Low expression of CTBP2 and CASP8AP2 correlated with poor outcome and predicted risk of relapse in pediatric B-cell acute lymphoblastic leukemia (B-ALL). This study aimed to investigate the molecular mechanism by which CASP8AP2 regulates LEF1 expression by interacting with CtBP2 and ZEB2 in Acute lymphoblastic lymphoma (ALL). There was an interaction between CASP8AP2, ZEB2, and CtBP2, and then the interaction between CtBP2 and ZEB2 was observed after downregulating the expression of CASP8AP2. The wild type (containing the ZEB2 binding site) or mutant (containing a mutant binding site) LEF1 gene promoter sequence was inserted into the pGL3-basic plasmid, and a dual-luciferase reporter gene detection system was used to observe how CASP8AP2, ZEB2, and CtBP2 regulate the transcription of the LEF1 gene. We conclude that CASP8AP2, CtBP2, and ZEB2 can all bind to the LEF1 gene promoter region and reduce the luciferase activity of the LEF1 promoter. Meanwhile, the interaction of ZEB2 and the LEF1 promoter was significantly weakened after downregulation of CASP8AP2. Knockdown of CASP8AP2 in the 697 cell lines resulted in the significant upregulation of the mRNA expression levels of the stemness-related genes CD44, JAG1, and SALL4 . In conclusion, CASP8AP2 is vital for the interaction between CtBP2 and ZEB2, inhibiting LEF1 and stemness-related genes expression ALL. Supplemental data for this article is available online at https://doi.org/10.1080/08880018.2022.2033369 .